The role of regional knowledge production in university technology transfer: Isolating coevolutionary effects - Marcel Hülsbeck; Erik E. Lehmann (University of Augsburg, Chair of Management and Organization, 2010)
The rate and magnitude of university-to-industry-technology-transfer (UITT) is a function not only of university characteristics but also of regional factors. A university's embeddedness in an innovative regional milieu moderates UITT. This necessary balance of the supply side (technology push) and demand side (market pull) of technology transfer has so far neither been systematically addressed in the technology transfer literature nor has it been acknowledged by policy makers.We investigate UITT as a function of the interrelation of the industrial innovative milieu of a region and the characteristics of regional universities to identify the impact of the industry on UITT. Thereby we do not only aim to reduce the existing empirical gap in the academic entrepreneurship literature but also to inform policy in its attempt to foster UITT in European regions.
Keywords: M13; O18; O32; 650; Regional Economics; Technology Transfer; Innovation; Endogenous Growth